Exploring MSME Owners’ Expectations of Data-Driven Approaches to Business Process Management - Gelmar García-Vidal; Alexander Sánchez-Rodríguez; Laritza Guzmán-Vilar; Rodobaldo Martínez-Vivar; Reyner Pérez-Campdesuñer (Systems)
This study explores the adoption of data-driven approaches to business process management (BPM) by micro, small, and medium enterprises (MSMEs), which are crucial for economic growth and job creation but often face challenges in adopting advanced technologies. The research aims to understand the perceived benefits and persistent barriers that MSMEs encounter when implementing data-driven BPM. A critical review of academic literature was conducted, focusing on factors influencing adoption, perceived benefits, and existing challenges. Literature consistently highlights benefits such as process optimization, informed decision making, customer personalization, operational efficiency, adaptability, risk mitigation, automation, organizational culture transformation, innovation, and transparency. However, the review also identifies significant challenges, including technological and infrastructural limitations, resource constraints, training and skill gaps, organizational and cultural resistance, data management and quality issues, difficulties in implementation and change management, and analytical and technical complexities. These findings emphasize that, while data-driven BPM offers substantial opportunities for MSMEs to improve competitiveness and efficiency, successful adoption requires careful consideration of these multifaceted challenges and the development of tailored strategies to overcome them.